Tinjauan Politik Hukum Oposisi dalam Pembentukan Undang-Undang Pemberantasan Korupsi - Devi Putri Thesia Panjaitan; Dwi Valentia Sihite; Eshaulin Br Sembiring; Pebriana Asina Panjaitan; Yosua Gabe Maruli Sijabat; Ramsul Nababan; Maulana Ibrahim (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The election of President Jokowi Dodo to the political elite seems to show intimacy in terms of policy formation. This can be seen in the formation of the draft KPK law which is basically not included in the national legislative program but was promulgated in a very short time and with a substance that seems to weaken Ad Hoc institutions. The Corruption Eradication Commission Bill has been passed and if changes are desired, it must involve all components of society, both legal experts and students. Seeing this, there is an instant and legal option, namely the establishment of government regulations in lieu of law. However, political conditions speak otherwise, in which all political parties do not want a Perpu. The role of the opposition is needed here as a balance controller who prioritizes the benefit of the people. Therefore, this research aims to review the role of the opposition in controlling the plan to establish the Corruption Eradication Law so that it remains fair in society. The research method used is a qualitative research method with a literature study approach. The research results show that basically the opposition acts as a check and balance against the government in power, such as monitoring the government, criticizing government policies, conveying community aspirations, providing alternative leadership, encouraging public discussion and debate. This aims to continue to prioritize the interests of the community.